Immunological characterization of IgG subclass deficiency reveals decreased Tregs and increased circulating costimulatory and regulatory immune checkpoints - Wågström, Per; Hjorth, Maria; Appelgren, Daniel; Björkander, Janne; Dahle, Charlotte; Nilsson, Mats; Nilsdotter-Augustinsson, Åsa; Ernerudh, Jan; Nyström, Sofia (Frontiers in Immunology, 2024)
Background: Immunoglobulin G subclass deficiencies (IgGsd) comprise a wide clinical spectrum from no symptoms to repeated respiratory infections and risk for the development of lung damage. Our aims were to investigate whether the immunological phenotype of IgGsd patients on and off immunoglobulin replacement therapy (IgRT) was reflected in the clinical features of IgGsd. Method: Thirty patients with IgGsd were included in this prospective study of 18 months of IgRT, followed by 7-18 months of IgRT discontinuation. Blood samples were collected when patients were on and off IgRT and compared with samples from 34 cross-sectional healthy controls. An in-depth lymphocyte phenotyping was performed by flow cytometry and plasma levels of immune checkpoints were assessed. Results: IgG3 subclass deficiency was most common. Patients with IgGsd had decreased levels of activated T cells and B cells and plasma levels of negative immune checkpoint molecules correlated negatively with T cell and B cell activation. The decreased T cell activation level was unaffected by IgRT, while the B cell activation was partly restored. Of note, decreased levels of activated regulatory T cells (Tregs) were found in IgGsd patients and was partly restored during IgRT. The profile of comorbidities did not associate with Treg levels. Conclusion: IgGsd is associated with decreased B cell and T cell activation including Tregs, and increased plasma levels of negative immune checkpoint molecules. The consequence of reduced activated Tregs in IgGsd remains unclear. Decreased immune cell activation was partly restored during IgRT, demonstrating that IgRT may contribute to improved immune function in patients with IgGsd.